Implementasi Aplikasi Absensi Siswa Berbasis Radio Frequency Identific Ation (Rfid) Di Smp Era Pembangunan III Jakarta - Khoiruddin, Adnan; Syam, Syahriani; Komalasari, Nia; Muryanah, Siti (Universitas Islam Syekh Yusuf Tangerang, 2025)
Manual student attendance recording is still widely used in schools and may lead to delays, recording errors, and limited transparency for parents. This study aims to design and implement a student attendance system based on Radio Frequency Identification (RFID) integrated with WhatsApp notification services as a replacement for manual methods at SMP Era Pembangunan III Jakarta. The research employs a software engineering approach using the Waterfall development model, which consists of requirements analysis, system design, implementation, testing, and maintenance. The system is developed as a web-based application using the Laravel framework and MySQL database, and utilizes a 125 kHz RFID reader device. Functional testing is conducted using the Blackbox Testing method on all main system features. The test results indicate that all system functions operate in accordance with the specified requirements, including automatic attendance recording and real-time attendance notification delivery to parents. The developed system is able to improve the efficiency of school administration and strengthen parental involvement in monitoring student attendance..